2006
DOI: 10.1037/0022-006x.74.2.393
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of a brief, mailed intervention for symptoms of depression.

Abstract: This research evaluated the efficacy of a brief, mailed personalized feedback intervention designed to alleviate depressed mood and antecedents (ineffective coping and hopelessness). College students (N = 177) were randomly assigned to intervention or control group following a baseline assessment. A week after completing the baseline assessment, participants in the intervention condition were mailed feedback and information detailing their mood, coping strategies, as well as suggestions for enhancing mood. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 67 publications
2
55
0
Order By: Relevance
“…Others have shown feedback to be promising when provided to students sanctioned for violating campus substance use policies (Fromme & Corbin, 2004;White et al, 2006). Finally, brief mailed feedback was shown to be successful in reducing depressed mood in college students (Geisner, Neighbors, & Larimer, 2006). These results suggest that personalized feedback may be effective in targeting other at-risk groups.…”
Section: Personalized Feedback For Selective Prevention: At-risk Groupsmentioning
confidence: 61%
See 2 more Smart Citations
“…Others have shown feedback to be promising when provided to students sanctioned for violating campus substance use policies (Fromme & Corbin, 2004;White et al, 2006). Finally, brief mailed feedback was shown to be successful in reducing depressed mood in college students (Geisner, Neighbors, & Larimer, 2006). These results suggest that personalized feedback may be effective in targeting other at-risk groups.…”
Section: Personalized Feedback For Selective Prevention: At-risk Groupsmentioning
confidence: 61%
“…Personalized feedback about depression symptoms and a depression tips brochure were also provided. Details of the depressed mood intervention and its efficacy are presented elsewhere (see Geisner et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive behavioral therapy may well form the key to changing patients' perception, although it may be necessary to use it in combination with anti-depressant treatment in more severe cases. Although conducted in college students, a recent randomized controlled trial using a brief mailed intervention for depressive symptoms as the mainstay of treatment also offers hope to patients characterized by feelings of hopelessness (Geisner et al 2006). The latter study showed that a reduction in depressive symptoms was partly mediated by a reduction in hopelessness, emphasizing the importance of the therapist instilling hope of change in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma, cost, and other barriers could prevent those who may need services from seeking them (Harris & Edlund, 2005; Ross, 2004; SAMHSA, 2008). Providing individuals with personalized information about their symptoms in private (via the web) could enable them to prevent escalation of symptoms and problems and facilitate future treatment seeking if needed (Geisner, Neighbors, & Larimer, 2006; Patel, Branch, Mottur-Pilson, & Pinard, 2004; Sirey, Bruce, & Alexopoulos, 2005). …”
Section: Introductionmentioning
confidence: 99%